2012
DOI: 10.5005/jp-journals-10024-1178
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of DIAGNOdent and Caries Detector Dye in Detection of Residual Caries in Prepared Cavities

Abstract: Aim:The objective of this study was to determine the association between DIAGNOdent laser and caries detector dye in detection of the remaining caries in restorative cavities. Materials and methods:The sample consisted of 100 cavities prepared in patients referring to the Department of Restorative Dentistry of Mashhad Dental School. After confirming caries absence by tactile examination, the presence of any residual caries was determined by a laser fluorescence (LF) device (DIAGNOdent Pen) and then by caries d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…[ 27 ] It has been demonstrated that fluorescent-based systems are suitable for visual detection of caries lesions. [ 28 29 ] In this study, VistaCam iX was employed to capture fluorescent images. A previous study indicated that this fluorescent camera provides high reproducibility and good performance for caries detection at various stages of the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…[ 27 ] It has been demonstrated that fluorescent-based systems are suitable for visual detection of caries lesions. [ 28 29 ] In this study, VistaCam iX was employed to capture fluorescent images. A previous study indicated that this fluorescent camera provides high reproducibility and good performance for caries detection at various stages of the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…This device is small and portable and thus easily applied in the clinical situation. It has been demonstrated that fluorescent-based systems are suitable for detection of caries lesions and assessing alteration in mineral level of tooth structure (17,24-26). Jablons-ki-Momeni et al (27) exhibited that VistaCam iX provides high reproducibility and good performance for caries detection at various stages of the disease process.…”
Section: Discussionmentioning
confidence: 99%
“…DIAGNOdent (DD) groups, utilizing the LF technology, comprised the largest number of studies included in this meta-analysis. There are two DD devices: DIAGNOdent 2095 (DD 2095) and DIAGNOdent pen 2190 (DD pen) [28,80]. DD 2095 works only on occlusal surfaces, whereas the DD pen works on both occlusal and proximal surfaces [81][82][83].…”
Section: Laser Fluorescence Technologymentioning
confidence: 99%